Scientific argumentation and responsive teaching: Using dialog to teach science in three middle‐school classrooms. Issue 6 (8th June 2022) - Felton, Mark; Levin, Daniel M.; De La Paz, Susan; Butler, Cameron
Abstract: Despite broad consensus on the value of classroom dialog for promoting scientific argumentation, tensions have emerged in the literature regarding the degree to which teachers should guide the dialogic process (dialogic stance). We use the lens of responsive teaching to examine how one teacher adjusts his instruction to foster dialog in three middle‐school science classrooms. Applying grounded theory to classroom dialogs and teacher interview data, we examine the dynamic interplay of the teacher's overarching goal and moment‐to‐moment pedagogical aims to understand shifts in his dialogic stance. Our findings illustrate the value of foregrounding responsiveness to students' disciplinary thinking when offering guidance to teachers about when and how to support students in peer‐based argumentative dialog.